Multiphysics SPH simulations with local particle coarsening - Ulrich, Christian; Bednarek, Sven; Rung, Thomas (ASME, 2011)
The paper reports on Smoothed-Particle-Hydrodynamics (SPH) for multi-physics water/soil interaction computations with dynamic particle coarsening. The procedure is supposed to be applied to harbour and ocean engineering hydrodynamic problems focussing on sediment scouring. This type of simulation usually implies large computational domains, fluid-soil interaction and complex geometries leading to large numbers of particles. To achieve a reasonable time-to-solution even for full-scale simulations, effective strategies to increase the computational performance are needed. We present a dynamic particle refinement/ coarsening strategy based on variable particle masses and spacings. The particle properties are updated in accordance to their current location. Validation studies refer to different water/ soil interaction test cases. Results obtained from the present refinement/coarsening approach show an encouraging predictive and computational performance.